2013
DOI: 10.1080/03235408.2013.823714
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sex ratio and adult longevity ofHabrobracon hebetorSay in relation to some conventional and biorational insecticides

Abstract: Habrobracon hebetor Say (Hymenoptera: Braconidae) is one of the most important natural enemies that has been used for biological control of lepidopteran pests, so the sub-lethal effects of imidacloprid, abamactin and Bacillus thuringiensis Berliner (Bt) on progeny sex ratio (male/total) and adult longevity of H. hebetor were examined under laboratory conditions. It was found that the progeny sex ratio changed to male bias significantly by Bt treatment. Also, the adult longevity of the wasp was affected adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Pesticides are a globally important tool in the control of pests and diseases in commercial crop systems; however, their use can adversely affect non‐target populations of arthropods, with both lethal and sublethal effects reported for a wide range of species . In recent years, the focus has turned more towards the sublethal effects on non‐target species; this is partly due to the potentially prolonged exposure of both target and non‐target species to sublethal concentrations in real conditions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticides are a globally important tool in the control of pests and diseases in commercial crop systems; however, their use can adversely affect non‐target populations of arthropods, with both lethal and sublethal effects reported for a wide range of species . In recent years, the focus has turned more towards the sublethal effects on non‐target species; this is partly due to the potentially prolonged exposure of both target and non‐target species to sublethal concentrations in real conditions …”
Section: Introductionmentioning
confidence: 99%
“…Pesticides are a globally important tool in the control of pests and diseases in commercial crop systems; 1-3 however, their use can adversely affect non-target populations of arthropods, with both lethal and sublethal effects reported for a wide range of species. [4][5][6][7][8] In recent years, the focus has turned more towards the sublethal effects on non-target species; 9,10 this is partly due to the potentially prolonged exposure of both target and non-target species to sublethal concentrations in real conditions. 11 Sublethal effects such as reproduction changes are studied in non-target arthropods as part of regulatory pesticide testing, 12 and many studies have reported negative effects at recommended field rates.…”
Section: Introductionmentioning
confidence: 99%
“…The observed alteration in sex ratio could potentially be attributed to the in uence of insecticide pressure during the fertilization process and/or the target speci city of insecticides associated with a particular sex before the eclosion of adults from pupae (Idris and Gra us, 1993). Many more investigations have suggested the possibilities of sex ratio adjustment due to insecticides application in various arthropods (Teather et al 2005;Kalajahi et al 2014). The production of males in insects is a pivotal factor in uencing population growth and diminishing the intrinsic rate of increase.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was no signi cant difference in the per cent corrected mortality among emamectin benzoate, emamectin benzoate + lufenuron, and novaluron + emamectin benzoate (Table2). Fecundity of S. frugiperda was also signi cantly reduced in spinetoram (2.93 eggs/female/day) as compared with other treatments and control (F(7,39) = Mortality of 3rd instar of Spodoptera frugiperda treated with Ad-hoc approved synthetic insecticides with toxicity coe cient (% E).…”
mentioning
confidence: 94%